ANALYSIS ON THE RELATIONSHIP OF EXTROVERT – INTROVERT PERSONALITY AND STUDENTS’ SPEAKING PERFORMANCE - Lestari, Arie; Sada, Clarry; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This study is an attempt to investigate the probable roles of extrovert-introvert personality towards speaking performance of the 2013 academic year students of English Education Study Program in FKIP UNTAN. To achieve such a purpose, 33 students were selected on the basis of availability sampling procedure and their personality type was determined by using Mark Parkinson Personality Questionnaire. Then the writer summarized and analyzed students’ midterm speaking scores. The personality and the students score were correlated by using Pearson Product Moment. The result of t-test revealed that there is statistically significant difference between the personality types of the participants’ speaking performance. There is also a different learning style between the introvert and extrovert students, introvert students prefer to study alone while the extroverts prefer to participate and study in group. Hopefully this research can be useful for achieving more effective English teaching and learning process.   Keywords: extrovert, introvert, speaking, performance Abstrak: Penelitian ini merupakan upaya untuk menyelidiki kemungkinan peranan kepribadian ekstrovert introvert terhadap kemampuan berbicara mahasiswa Program Studi Pendidikan Bahasa Inggris tahun akademik 2013 di FKIP UNTAN. Untuk mencapai tujuan tersebut, 33 siswa dipilih berdasarkan prosedur ketersediaan sampling dan tipe kepribadian mereka ditentukan dengan menggunakan Kuesioner Kepribadian Mark Parkinson. Kemudian penulis menyimpulkan dan menganalisa hasil ujian tengah semester berbicara mahasiswa. Hasil kuisoner kepribadian dan skor siswa dalam berbicara dikorelasikan dengan menggunakan Pearson Product Moment. Hasil uji t menunjukkan bahwa ada perbedaan yang signifikan antara tipe kepribadian peserta dalam penelitian dan kemampuan berbicara mereka. Terdapat pula perbedaan gaya belajar antara siswa  introvert dan ekstrovert, siswa introvert lebih suka belajar sendiri sementara siswa ekstrovert lebih memilih untuk berpartisipasi dan belajar dalam kelompok. Semoga penelitian ini dapat bermanfaat untuk mencapai proses pengajaran dan pembelajaran  bahasa Inggris yang lebih efektif. Kata kunci: ektrovert, introvert, berbicara, prestasi